Negative Effects of Revealing AI Involvement in Products: Mediation by Authenticity and Risk, Moderation by Trust in AI and Familiarity with AI - Gedas Kučinskas (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Background: With artificial intelligence (AI) technologies developing at a rapid pace, there is increasing interest in learning how disclosed AI involvement affects customer perceptions and purchasing choices of AI generated products. This study aims to explore the impact of AI involvement in product creation on consumer perceptions across different product categories. Materials and Methods: A series of experimental studies were conducted using three product types: books, e-books and print canvas. Participants were exposed to products with varying levels of AI involvement, and their perceptions of authenticity, quality, financial risk, and willingness to pay were assessed using self-reported measures. Results: The results revealed significant differences in consumer perceptions based on AI involvement. Products with disclosed AI involvement were associated with lower authenticity, quality, and willingness to pay compared to human-authored products. Additionally, the study identified performance risk and perceived authenticity as significant mediators in the relationship between AI involvement and consumer perceptions. Conclusion: The findings suggest that consumers generally prefer products perceived to be human-authored over those involving AI, particularly in terms of authenticity and perceived quality. These perceptions significantly influence consumer willingness to pay and purchase intent. Grasping these dynamics is essential for companies seeking to incorporate AI technologies into their product development and marketing efforts, suggesting that revealing AI involvement could be risky.